Prevalence of serotypes causing invasive pneumococcal disease in the region of Tarragona, Spain, 2006-2009: vaccine-serotype coverage for the distinct antipneumococcal vaccine formulations - Ochoa-Gondar, Olga; Gómez-Bertomeu, Frederic; Vila-Córcoles, Angel; Raga, Xavier; Aguirre, Carlos; Utrera, Jesús; de Diego, Cinta; Guzmán, Jorge A; Figuerola, Enric (Revista española de quimioterapia, 2015)
Pneumococcal infections remain a major health problem worldwide. This study analysed the distribution of distinct Streptococcus pneumoniae serotypes causing invasive pneumococcal disease (IPD) among all-age population in the region of Tarragona (Spain) throughout 2006-2009. An amount of 237 strains were evaluated, of which 203 (85.7%) were isolated from blood cultures, 14 (5.9%) from pleural fluids, 13 (5.5%) from CSF samples and 7 (3%) from other sterile sites. Forty-seven cases (19.8%) were children ≤ 14 years, 94 (39.7%) were patients 15-64 years and 96 (40.5%) were patients ≥ 65 years. Seven serotypes (1, 3, 6A, 7F, 12F, 14 and 19A) caused almost two thirds (63.3%) of cases among all-age patients. Serotype 1 was the most common serotype among children (44.7%) and among people 15-64 years (21.3%), whereas serotype 19A was the most common among people ≥ 65 years (12.5%).Among all-age population, serotype-vaccine coverage for the distinct pneumococcal polysaccharide vaccine (PPV) and conjugate vaccines (PCVs) were 17.3% for the PCV7, 49.8% for the PCV10, 73% for the PCV13 and 80.2% for the PPV23 (p < 0.001). Among children, vaccine-serotype coverage was 23.4% for the PCV7, 72.3% for the PCV10 and 83% for the PCV13. Among people ≥ 65 years, vaccine-serotype coverage was 62.5% for the PCV13 and 68.8% for the PPV23. A considerable proportion of IPD cases among our population would not be covered by the current pneumococcal vaccines.